Cryo-EM Structure Reveals Polymorphic Ligand-bound States of IGF1R. Issue 9 (15th May 2022) - Zhang, Xi; Wei, Tianzi; Wu, Cang; Jiang, Junyi; Chen, Shengming; Hu, Yinqing; Lu, Yi; Sun, Dayong; Zhai, Liting; Zhang, Jian; Liu, Chuang
Graphical abstract: Highlights: Cryo–EM structures show the polymorphic ligand-bound states of IGF1R. The orientation of α-CT 2, disulfide bond (C670-C670′) and FnIII-2 domains was the most flexible parts for the conformation change when ligand binds to the receptor. These results illustrated the mechanism of how different ligands could bind to human IGF1R, and provided a rational template for drug design. Abstract: Type 1 insulin-like growth factor receptor (IGF1R) plays an important role in regulating cellular metabolism and cell growth and has been identified as an anticancer drug target. Although previous studies have revealed some structures of IGF1R with different ligands, the continuous dynamic conformation change remains unclear. Here, we report 10 distinct structures (7.9–3.6 Å) of IGF1R bound to IGF1 or insulin to reveal the polymorphic conformations of ligand-bound IGF1R. These results showed that the α-CT 2, disulfide bond (C670-C670′), and FnIII-2 domains had the most flexible orientations for the conformational change that occurs when ligands bind to the receptor. In addition, we found one special conformation (tentatively named the diverter-switch state) in both complexes, which may be one of the apo-IGF1R forms under ligand-treatment conditions. Hence, these results illustrated the mechanism of how different ligands could bind to human IGF1R and provided a rational template for drug design.